Language development and developmental language disorder - Jordens, Peter (Studies on Language Acquisition [SOLA] Ser., 2022)
Acquisition of the native language proceeds in a stage-wise manner for both typically developing (TD) children and children with developmental language disorder (DLD). As shown in TD children learning Dutch and German, the ability to establish contextual cohesion serves as the driving force to proceed from a simple, lexical system to a more complex, functional system. It is argued that precisely this ability is challenged in children with DLD. The present book offers an account of the functional linguistic features fit to achieve contextual cohesion in language production. It provides a rationale for practitioners to develop linguistically founded tools to be used in speech therapy.